The Air-Sea Nitrous Oxide Flux along Cruise Tracks to the Arctic Ocean and Southern Ocean - Liyang Zhan; Man Wu; Liqi Chen; Jixia Zhang; Yuhong Li; Jian Liu (Atmosphere, 2017)
Nitrous oxide is a trace gas with two global environmental effects: it depletes stratospheric ozone and contributes to the greenhouse effect. Oceans are one of the most significant nitrous oxide sources; however, there are ocean areas whose contributions to the nitrous oxide budget are not yet well studied. The Southern Ocean and the Arctic Ocean feature strong winds and portions that are covered by sea ice. These intense environmental conditions and the remoteness of these regions hamper fieldwork; hence, very limited data are available on the distributions and the source and sink characteristics of nitrous oxide. Using data from the 4th Chinese National Arctic Research Expedition and the 27th Chinese National Antarctic Research Expedition, the first global-scale investigation of the surface water N2O distribution pattern, the factors influencing the N2O distribution and the air-sea N2O flux are discussed in this study. The results show that the tropical and subtropical regions (30° N–30° S) exhibit significant source characteristics, with a maximum air-sea flux of approximately 21.0 ± 3.9 μmol·m−2·d−1. The high air-sea flux may result from the coastal influences and high wind speeds in certain areas. The distribution patterns of N2O in the sub-polar regions (30° N–60° N, 30° S–60° S) transition from oversaturated to approximate equilibrium with the atmosphere, and the boundaries generally correspond with frontal structures. The distributions of N2O in the high-latitude Southern Ocean and Arctic Ocean (>60° N and 60° S) exhibit contrasting patterns. With the exception of the continental shelf hotspot, the Arctic Ocean surface water is undersaturated with N2O; in contrast, the high-latitude Southern Ocean along the cruise track is oversaturated with N2O. The high-latitude Southern Ocean may act as a N2O source, with a maximum air-sea N2O flux of approximately 9.8 ± 0.5 μmol·m−2·d−1 at approximately 60° S, whereas the air-sea N2O flux of the Arctic Ocean is close to zero due to the low wind speed conditions at these latitudes.